Problem-Solving Ability Through the Fast Feedback Method with a Student Answer Grouping Model - Sumarni, Sumarni; Marsitin, Retno; Ferdiani, Rosita Dwi (Department of Mathematics Education, Faculty of Teacher Training and Education, Wisnuwardhana University of Malang, 2025)
A common problem in mathematics learning is teachers' delays in providing feedback to students, thus slowing down the process of conceptual understanding. The Fast Feedback method allows teachers to respond quickly to students' answers during learning activities. This study aims to improve students' mathematical problem-solving skills through the Fast Feedback method with an answer grouping model. This study used a Classroom Action Research (CAR) approach implemented in three cycles with the stages of planning, implementation, observation, and reflection. The subjects were 42 students of SMP Harmoni School Terpadu Teluk Bintuni Regency, studying the Pythagoras Theorem. Data was collected through task cards, observation sheets, and documentation. The results showed an increase in students' problem-solving skills in each cycle. The number of students answering correctly increased from 31 students in cycle I to 38 students in cycle II, and 39 students in cycle III. Thus, the application of the Fast Feedback method with an answer grouping model has been proven to improve students' mathematical problem-solving skills. The Fast Feedback method using the answer grouping model is expected to be used in in-depth mathematics learning and have an impact on efforts to improve student learning outcomes